Jardim Do Embaixador: Uma Arquitetura Experimental De Oswaldo Bratke Nos Anos 1940 - Leite, Marcelo Andre Ferreira [UNIFESP] (2018)
The Dominant Narrative Plot Of Modern Brazilian Architecture Has Given More Space To Large Urban Centers, Use Of Techniques Such As Reinforced Concrete And Steel, Genius Architecture, Public Or Institutional Works, And The Almost Messianic Role Of The Franco- Swiss Architect Le Corbusier. In This Context, The São Paulo Architect Oswaldo Arthur Bratke (1907-1997) Ended Up Relegated To A Secondary Position In History, Because He Was An Exponent Of The Architecture Of Office, To Have Devoted Himself Mainly To The Single-Family Residential Typology And Never To Have Caught On Doctrines, Preferring A Free And Multiple Search By References In Brazil And Abroad. The Neighborhood Jardim Do Embaixador (A"Bassador"S Garde"), An Enterprise Whose Conception, Urbanization And First Buildings Were Carried Out By Bratke In 1944, Is In The Town Of Campos Do Jordão, São Paulo " And Is An Inner Production, Made Of Wood And Stone, And Related With North American Architectures " Forgotten By Its Creator Who, After Becoming Emine